Bacterial Preferences for Specific Soil Particle Size Fractions Revealed by Community Analyses - Hemkemeyer, Michael; Dohrmann, Anja B.; Christensen, Bent T.; Tebbe, Christoph C. (Frontiers in Microbiology, 2018)
Genetic fingerprinting demonstrated in previous studies that differently sized soil particle fractions (PSFs; clay, silt, and sand with particulate organic matter (POM)) harbour microbial communities that differ in structure, functional potentials and sensitivity to environmental conditions. To elucidate whether specific bacterial or archaeal taxa exhibit preference for specific PSFs, we examined the diversity of PCR-amplified 16S rRNA genes by amplicon sequencing using total DNA extracted from long-term fertilization variants of an agricultural loamy sand soils and their PSFs. The PSFs were obtained by gentle ultrasonic dispersion, wet sieving, and centrifugation. The abundance of bacterial taxa assigned to operational taxonomic units (OTUs) differed less than 2.7 % between unfractionated soil and soil based on combined PSFs. Across the three soils no archaeal OTUs, but many bacterial OTUs, the latter representing 34 to 56 % of all amplicon sequences, showed significant preferences for specific PSFs. The sand-sized fraction with POM was the preferred site for members of Bacteroidetes and Alphaproteobacteria, while Gemmatimonadales preferred coarse silt, Actinobacteria and Nitrosospira fine silt, and Planctomycetales clay. Firmicutes were depleted in the sand-sized fraction. In contrast, archaea, which represented 0.8 % of all 16S rRNA gene sequences, showed only little preference for specific PSFs. We conclude that differently sized soil particles represent distinct microenvironments that support specific bacterial taxa and that these preferences could strongly contribute to the spatial heterogeneity and bacterial diversity found in in soils.